INTERNATIONAL IMPACT OF THE COVID-19 PANDEMIC LOCKDOWN ON INTRAVITREAL THERAPY OUTCOMES: Fight Retinal Blindness Registry. Issue 4 (April 2022) - Zarranz-Ventura, Javier; Nguyen, Vuong; Creuzot-Garcher, Catherine; Verbraak, Frank; O´Toole, Louise; Invernizzi, Alessandro; Viola, Francesco; Squirrel, David; Barthelmes, Daniel; Gillies, Mark C.; ,
Abstract : Supplemental Digital Content is Available in the Text. This study evaluates the impact of COVID-19 pandemic lockdown on intravitreal therapy outcomes in a large international cohort, benchmarks each individual country's performance, and explores intercountry differences to identify potential reasons for these variations. This report will serve clinicians to prepare strategies to avoid vision loss in future pandemics. Abstract : Purpose: To evaluate the impact of the COVID-19 pandemic lockdowns on the outcomes of eyes treated for neovascular age-related macular degeneration, diabetic macular edema, and retinal vein occlusion in eight countries. Methods: A multicenter international database study of 5, 782 eyes (4, 708 patients) receiving intravitreal antivascular endothelial growth factor injections before, during, and after national lockdowns. The baseline visit was defined as the last visit within 3 months before lockdown, and prelockdown and postlockdown periods were defined as 6 months before and after the lockdown date. Results: Eyes with neovascular age-related macular degeneration (n = 4, 649) lost vision in all countries in proportion to the reduced number of injections. The mean visual acuity change postlockdown ranged from −0.4 to −3.8 logarithm of the minimum angle of resolution letters, and the median number of injections/visits decreased from 4–5/4–7 to 2–4/2–4 postlockdown. The diabetic macular edema (n = 654) and retinal vein occlusion (n = 479) eyes' mean visual acuity change ranged from −2.8 to +1.7 letters and −1.6 to +0.1 letters, and the median number of injections/visits decreased from 2.5–5/4–6 to 1–3/2–4 and from 3–5.5/4–5 to 1–3.5/2–3.5, respectively. The 6-month dropout rates postlockdown were 20% for neovascular age-related macular degeneration, 27% for diabetic macular edema, and 28% for retinal vein occlusion. Conclusion: This international study provides estimates of the impact of COVID-19 pandemic lockdown on intravitreal therapy and suggests that prioritizing neovascular age-related macular degeneration eyes seems appropriate.